STUDIES ON GENETIC DIVERGENCE AND REACTION TO IRON CHLOROSIS IN AEROBIC RICE (ORYZA SATIVA L.) ON VERTISOLS IN MAHARASTRA - Ritesh Kumar Yadav, Rajeev Dhakal,; Paudel, Dhan Prasad; Deosarkar, D. B. (Journal of Plant Stress Physiology)
The present study was carried out to study the genetic parameters for yield, yield contributing, quality and nutritional characters along with reaction of genotypes against iron chlorosis in vertisols. The experiment consisted of 50 promising genotypes along with standard checks viz., Basmati-370, Parag and Avishkar were grown in randomized block design with three replications. The analysis of variance revealed that all the characters under study. Different genotypes showed some degrees of tolerance to iron chlorosis. And, some other characteristics like number of effective tillers per plant, number of filled grains per panicle, number of unfilled grains per panicle, gel consistency, flag leaf area, straw yield, grain yield per plot and grain yield per plant showed high estimates of phenotypic coefficient of variation, high heritability with high genetic advance. All characters which exhibited high estimates of both genotypic and phenotypic variance coupled with high heritability and high genetic advance can be employed for simple selection for crop improvement. Furthermore, variation in such characters are result of additive gene effects and can be explored and studied for potentialities of being used as parents in breeding program for improvement for particular traits.